Online purchase intention of hotel room reservations via online travel agents - Kok, Li-Ming Adeline (2019)
In Malaysia although most domestic consumers book their hotel room via hotel websites, the trend is towards online travel agents booking. Only 34 percent of domestic consumers book their hotel room via online travel agents. Hence, the main aim of this research is to empirically verify the determinants of consumers’ online purchase intention of hotel room reservation via online travel agents. The study employed a quantitative research approach to examine trust, perceived price, perceived usefulness and perceived ease of use and their relationships with consumers’ online purchase intention of hotel room reservation. The mediating effects of perceived usefulness and perceived ease of use are also examined. The survey instrument consists of 39 items. Through quantitative approach, 600 questionnaires were distributed to 600 domestic tourists in three states in Malaysia namely Selangor, Perak and Kuala Lumpur through hotel intercept method. 402 questionnaires were returned representing a 67 percent response rate. The data were analysed using structural equation modelling analysis method which produces eleven significant relationships. The findings of the study indicated that trust, perceived ease of use and perceived usefulness are significant direct determinants of online purchase intention of hotel room reservation. Perceived ease of use and perceived usefulness are found to mediate the relationships of perceived price and trust on online purchase intention of hotel room reservation. This study provides valuable insights to marketers of online travel agents and hotel marketers. Online travel agents and hotels can use the findings of this study to strategise more user-friendly and trustable websites that provide relevant information to consumers in order to encourage more online hotel room bookings.